Mempelajari Proses Produksi Checking Fixture (CF) Panel Unit Dengan Studi Kasus di PT. Fadira Teknik - Yoston Harada Sinurat; Marno Marno; Aa Santosa (Peneliti.net, 2022)
In line with the company's management policies, which requires to implement a Built In Quality (BIQ) system in the production line, make production operators required to check their products alone. So a checking tool is needed to make it easier and speed up product checking time, namely Checking Fixture (CF). With the presence of tools, operator skills needed to check not too high. Job Training Process which has been completed by the author on September 28 to October 28 at PT. Fadira Teknik includes case studies in the field aimed at knowing the stages of the process of one of the products produced by the PT, namely Checking Fixture (CF) as well as looking for several factors that affect the magnitude of failure in the product, one of which is failure in the calibration process